Progress of Rehabilitation Therapy for Cerebellar Ataxia after Stroke - Aijun CHENG; Lina TAN (康复学报)
By reviewing related literature at home and abroad, the paper summarized and analyzed the present situation of rehabilitation therapy in patients with cerebellar ataxia. The major therapeutic strategy included acupuncture, neural rehabilitation therapy, exercise therapy, physical therapy, contemporary medicine and traditional Chinese medicine dialectical application, traditional Chinese medicine combined with acupuncture therapy, etc.. The results revealed that combination of contemporary rehabilitation with traditional rehabilitation approach could enrich the clinical therapeutic tools of cerebellar ataxia after stroke, reduce the patient's dysfunction, and improve their ability of daily life activities more effectively.